Challenges in assessing the vulnerability of species to climate change to inform conservation actions. (July 2016) - Butt, N.; Possingham, H.P.; De Los Rios, C.; Maggini, R.; Fuller, R.A.; Maxwell, S.L.; Watson, J.E.M.
Abstract: Understanding climate change impacts on species is vital for correctly estimating their extinction risk and choosing appropriate conservation actions. We perceive four common challenges that hamper conservation planning for species affected by climate change: (i) only considering climate exposure in assessments of vulnerability to climate change, ignoring the two other components of vulnerability (sensitivity and adaptive capacity); (ii) treating climate change as a long-term, gradual threat without recognising that it will change the frequency and magnitude of climate extremes; (iii) treating climate change as a future threat, disregarding current impacts of existing change; and, (iv) focusing on direct impacts of climate change, ignoring its interactions with other threats. We describe the implications of these challenges and urge that establishing management objectives in relation to species' vulnerability is crucial for choosing effective and efficient conservation action. Highlights: Assessments of species' vulnerability to climate change are often used to estimate threats and direct conservation resources. We identify four challenges in how vulnerability is considered that prevent comprehensive assessments from being made. We discuss how to address these challenges and thus enable effective informing of conservation actions. We highlight the importance of using objective-based conservation planning frameworks.